Заметки о сознании культуры в семиотическом наследии Юрия Лотмана - Вершич , Саня (SlavVaria, 2022)
Notes on the Consciousness of Culture in the Semiotic Inheritance of Yuri Lotman. In the article, we bring attention to the phenomenon of consciuousness for which Lotman shows particular interest in his works on semiotics of culture, and we notice that the concept of consciousness is inherent in metamodels of culture developed by semiotician. Owing to Lotman's precious ideas, new possibilities appear in approaching questions of cultural consciousness.